2019
DOI: 10.3390/plants8030069
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Total Phenolic Content, In Vitro Antioxidant and Antibacterial Activity of Ruta graveolens L. Extracts Obtained by Choline Chloride Based Natural Deep Eutectic Solvents

Abstract: Rue (R. graveolens) has been an extensively studied medicinal plant due to its rich phytochemicals content, such as furanocoumarins and flavonoids. The aim of this study was to determine the effects of varying extraction conditions on the total phenolic content, the antioxidant and antibacterial property of rue leaves crude extracts using deep eutectic solvents with different water content. These extraction conditions include the temperature and the extraction time. The extract obtained at 30 °C, with 20% wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 32 publications
1
15
1
1
Order By: Relevance
“…In previous study, Shan et al [42] demonstrated good linear correlations of phenolic content with the antibacterial activity of medicinal herbs against foodborne bacteria including S. aureus (r 2 = 0.93). Pavić et al [52] also reported that TPC in a medicinal plant, namely Ruta graveolen L., was strongly correlated to the MIC values of E. coli, B. subtilis, and S. aureus (r = 0.973, p < 0.050). These results suggest that polyphenols might contribute to antibacterial properties of plant extracts.…”
Section: Correlations Analysis Among Polyphenolic Content Antibactermentioning
confidence: 95%
See 1 more Smart Citation
“…In previous study, Shan et al [42] demonstrated good linear correlations of phenolic content with the antibacterial activity of medicinal herbs against foodborne bacteria including S. aureus (r 2 = 0.93). Pavić et al [52] also reported that TPC in a medicinal plant, namely Ruta graveolen L., was strongly correlated to the MIC values of E. coli, B. subtilis, and S. aureus (r = 0.973, p < 0.050). These results suggest that polyphenols might contribute to antibacterial properties of plant extracts.…”
Section: Correlations Analysis Among Polyphenolic Content Antibactermentioning
confidence: 95%
“…Although the spectrophotometric methods such as Folin-Ciocalteu method and AlCl 3 -based colorimetric method are commonly used to quantify total phenolics in plant extracts [52][53][54][55][56][57], these analyses are not accurate measurements. The Folin-Ciocalteu assay can contribute to the overestimation of TPC due to the presence of reducing compounds such as ascorbic acid, reducing sugars, and aromatic amino acids (tyrosine and tryptophan), leading to the disruption of phenolic oxidation reaction [58][59][60][61].…”
Section: Total Phenolic Content (Tpc) and Total Flavonoid Content (Tfmentioning
confidence: 99%
“…Due to their chemical composition, several studies have indicated that Ruta graveolens (rue) has potent antimicrobial activity. Besides, topical pharmaceutical fungicides were prepared from rue extracts [31,32,33,34,35,36,37,38,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…In the long term, would their use lead to a shortened lifetime of the extractors and the analytical tools needed for their identification and quantification? All the above questions remain open and certainly offer many possibilities that can be answered in the future [26,168,169].…”
mentioning
confidence: 99%